Pressure-driven switching of magnetism in layered CrCl3. Issue 45 (12th November 2020) - Ahmad, Azkar Saeed; Liang, Yongcheng; Dong, Mingdong; Zhou, Xuefeng; Fang, Leiming; Xia, Yuanhua; Dai, Jianhong; Yan, Xiaozhi; Yu, Xiaohui; Dai, Junfeng; Zhang, Guo-jun; Zhang, Wenqing; et al.
Abstract : Pressure-induced switching of magnetism from FM to AFM phase has been observed in layered CrCl3 . Concurrently, pressure-induced isostructural transition accompanied with an unusual semiconductor-to-semiconductor transition has been reported. Abstract : Layered transition-metal compounds with controllable magnetic behaviors provide many fascinating opportunities for the fabrication of high-performance magneto-electric and spintronic devices. The tuning of their electronic and magnetic properties is usually limited to the change of layer thickness, electrostatic doping, and the control of electric and magnetic fields. However, pressure has been rarely exploited as a control parameter for tailoring their magneto-electric properties. Here, we report a unique pressure-driven isostructural phase transition in layered CrCl3 accompanied by a simultaneous switching of magnetism from a ferromagnetic to an antiferromagnetic ordering. Our experiments, in combination with ab initio calculations, demonstrate that such a magnetic transition hinders the bandgap collapse under pressure, leading to an anomalous semiconductor-to-semiconductor transition. Our findings not only reveal the potential applications of this material in electronic and spintronic devices but also establish the basis for exploring unusual phase transitions in layered transition-metal compounds.